Analisis Website UNMAHA Menggunakan Google Analytics dan SEOQuake - Adi Mahendra (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Abstract The UNMAHA campus has a website with the address unmaha.ac.id as a medium of information, the website is still relatively new. Therefore it is necessary to analyze the UNMAHA Website which has the aim of conducting a UNMAHA Site Analysis with Google Analytics and SEOQuake Tools, and to find out the comparison between the performance of the Google Analytics and SEOQuake Tools on the UNMAHA Website. The first step is to analyze the unmaha.ac.id website with several tools including Google Analytics and SEOQuake then carry out the second step, namely Keyword Research, Competitor Research, Internal SEO, External SEO, and Website Page Speed ​​Optimization. The results of the analysis of the comparison of the performance of Google Analytics and SEOQuake on the Mahakarya Asia University Website. Keywords— Google Analytics, SEOQuake, Website